Remote and in-Situ Characterization of Mars Analogs: Coupling Scales to Improve the Search for Microbial Signatures on Mars - Harris, Carolynn M.; Maclay, Matthew T.; Lutz, Katherine A.; Nathan, Vinitra; Ortega Dominguez, Noemi A.; Leavitt, William D.; Palucis, Marisa C. (Frontiers in Astronomy and Space Sciences, 2022)
Past environments on Mars contained abundant water, implying the potential for microbial inhabitants. Gale and Jezero craters, home of the Perseverance and Curiosity rovers, hosted ancient lakes that experienced periods of active hydrologic cycling and prolonged drying intervals. Exploration of these basins will benefit from detailed characterizations of analogous environments on Earth, where life detection strategies at various spatial scales can be tested and validated. Investigations of terrestrial analogs are critical for understanding (1) how microorganisms generate chemical biosignatures in environments characterized by multiple extreme conditions; (2) the impact of environmental conditions and mineralogy on biosignature preservation; and (3) what technologies and techniques are needed to detect biosignatures remotely or in situ. Here, we survey five terrestrial sites analogous to climate conditions proposed for Late Noachian to Early Hesperian Mars, when craters are thought to have hosted active lakes. We review the geologic setting, environmental conditions, microbial habitability, extant microbial communities, and preserved biomarkers at each analog and discuss their relevance to the search for signs of life in martian craters. The analogs range from active to desiccated lake systems, temperate to hyper-arid climates, and have acidic to neutral-pH and hypo- to hyper-saline waters. Each analog hosts microorganisms adapted to multiple extremes, including aspects of water availability and physiochemistry that can form macrobiological features such as microbial mats. Comparing the expected achievable spatial resolution of several key Mars instruments to the spatial extent of macrobiological features at each analog reveals that most features are unlikely to be resolved from orbit and require rover-scale instruments for detection. We recommend that future studies at these analogs employ multi-scale remote sensing surveys to determine thresholds for detecting macrobiological features and map how patterns in mineralogy or physical characteristics of environments correlate to modern-day microbial communities or preserved biomarkers. It will also be critical to determine how the characteristics of macrobiological features impact detectability thresholds. These findings can provide vital information on potential topographic or spectroscopic signatures of life, and at what scales they are detectable. This research is critical to guide sample collection locations within craters like Jezero.